Sustainability of groundwater through community-driven distributed recharge: an analysis of arguments for water scarce regions of semi-arid India - Patel, Praharsh M.; Saha, D.; Shah, Tushaar (Elsevier, 2020)
Study Region: Semi-Arid Regions of Marathawada, Vidarbha and Saurashtra in India Study Focus: To understand and evaluate the impact of Managed Aquifer Recharge (MAR) efforts. New Hydrological Insights for the Region: Since 1990, the Saurashtra region of Gujarat, India witnessed a massive community-based distributed groundwater recharge movement, initially catalyzed by NGOs and later supported by the government. The region has witnessed visible improvement in groundwater resources during recent years, which was attributed by some researchers to the recharge movement. A competing hypothesis holds that improvement in groundwater levels in Saurashtra are a result more due to a succession of good rainfall years during 2001–2014, aided by transfer of surface water from a big dam on Narmada River, rather than the distributed recharge movement. We develop and implement a 2-way test of these competing hypotheses: First, we compare groundwater recharge patterns in Saurashtra during a recent period of high rainfall years with a similar period before the onset of the recharge movement; second, for both these high rainfall periods, we also compare groundwater recharge patterns in two other comparable aquifer and terrain regions, viz., Vidarbha and Marathawada in Maharastra, which did not experience recharge movement on the same scale as Saurashtra did. Our results support the hypothesis that the community supported distributed recharge movement is the key to improved groundwater recharge in Saurashtra during 2004-09.